Impact of globalization on human rights: evidence from Sub-Saharan Africa. Issue 12 (2nd November 2020) - Takiyar, Aman; Rao, N.V.M.
Abstract : Purpose: The purpose of this study is to examine the impact of globalization and its multiple dimensions on human rights in Sub-Saharan Africa. Design/methodology/approach: The study extends the Poe and Tate (1994) model, which enumerates the various determinants of human rights. Ordered probit estimation is used to estimate the impact of globalization and its dimensions. For the purpose of empirical analysis, the period has been divided into three phases: short, medium and long term. This helps in understanding how the impact of the different dimensions of globalization has evolved over a period of time. Furthermore, analysis has been carried out to detect causality between human rights and globalization. Findings: As per the results, overall globalization and social dimension of globalization do have a positive impact on human rights in long and medium term and, also, Granger-cause human rights. The political dimension of globalization has a positive relation with human rights, though there exists no causality between the two. On the other hand, the economic dimension of globalization fails to have a statistically significant impact on human rights. Impact of the social dimension of globalization dominates that of other dimensions of globalization. Originality/value: This is one of the few studies that examine, in an empirical fashion, the impact of globalization on human rights in Sub-Saharan Africa.